Лекарственные и съедобные растения Удмуртии: справочник / В. В. Туганаев - Туганаев Виктор Васильевич (Удмуртия, 2018)
Экземпляры: аб. ЦБ (20200818) / Инвентарный номер: 7896 / Цена: / Сис.шифр: 42.143 / Авт.знак: Т 81 / ГРНТИ: 68.35 / ББК: 42.143